An automated device for provoking and capturing wildlife calls - David E. Ausband; Jesse Skrivseth; Michael S. Mitchell (Wildlife Society Bulletin)
Abstract Some animals exhibit call‐and‐response behaviors that can be exploited to facilitate detection. Traditionally, acoustic surveys that use call‐and‐respond techniques have required an observer's presence to perform the broadcast, record the response, or both events. This can be labor‐intensive and may influence animal behavior and, thus, survey results. We developed an automated acoustic survey device using commercially available hardware (e.g., laptop computer, speaker, microphone) and an author‐created (JS) software program (“HOOT”) that can be used to survey for any animal that calls. We tested this device to determine 1) deployment longevity, 2) effective sampling area, and 3) ability to detect known packs of gray wolves (Canis lupus) in Idaho, USA. Our device was able to broadcast and record twice daily for 6–7 days using the internal computer battery and surveyed an area of 3.3–17.5 km2 in relatively open habitat depending on the hardware components used. We surveyed for wolves at 2 active rendezvous sites used by closely monitored, radiocollared wolf packs and obtained 4 responses across both packs over 3 days of sampling. We confirmed reproduction in these 2 packs by detecting pup howls aurally from the resulting device recordings. Our device can broadcast and record animal calls and the computer software is freely downloadable. This automated survey device can be used to collect reliable data while reducing the labor costs traditionally associated with acoustic surveys. © 2011 The Wildlife Society.